PENGEMBANGAN BAHAN AJAR BERBASIS REALISTIC MATHEMATICS EDUCATION UNTUK MENINGKATKAN KEMAMPUAN LITERASI MATEMATIS PESERTA DIDIK KELAS VII SMP - Putri, Amelia Defrianti (Jurnal Edukasi dan Penelitian Matematika, 2023)
The Curriculum changes make teachers have to be creative in developing teaching materials because there are not many teaching materials that apply an independent curriculum. So that the existing teaching materials are still lacking to facilitate the learning process.Realistic Mathematics Educationbased teaching materials that are valid and practical are the goal of this study. This teaching material uses the Plomp development modelwhich consists of twophase, namely the preliminary phase and the development phase. This research was conducted on class VII students of SMP Pembangunan Laboratorium UNP. Data collection instruments used were observation, interviews, and questionnaires. In this research obtained teaching materials based on realistic mathematics education with a validity value of 91.16% in the very valid category and 95.62% practicality value in the very practical category. Keywords–Teaching Materials, Realistic Mathematics Education, Valid, Practical